2022
DOI: 10.3390/ijms23126422
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dynamic Movement of Polymerized Amyloid β in the Perivascular Space of the Cerebral Cortex in Mice

Abstract: Disposition of amyloid β (Aβ) into the perivascular space of the cerebral cortex has been recently suggested as a major source of its clearance, and its disturbance may be involved in the pathogenesis of cerebral amyloid angiopathy and Alzheimer’s disease. Here, we explored the in vivo dynamics of Aβ in the perivascular space of anesthetized mice. Live images were obtained with two-photon microscopy through a closed cranial window. Either fluorescent-dye-labeled Aβ oligomers prepared freshly or Aβ fibrils afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…However, the physiological role and detailed mechanisms of this system are still hypothetical, lacking dynamic data on "in vivo flow". Our previous study confirmed, for the first time, that Aβ can be transported from the cortical surface to the deeper parenchyma through the perivascular space, although there is a difference in the transportation speed between oligomers and fibrils [11]. In the narrow perivascular space, large Aβ fibrils may be easily trapped between the vascular wall and parenchyma.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the physiological role and detailed mechanisms of this system are still hypothetical, lacking dynamic data on "in vivo flow". Our previous study confirmed, for the first time, that Aβ can be transported from the cortical surface to the deeper parenchyma through the perivascular space, although there is a difference in the transportation speed between oligomers and fibrils [11]. In the narrow perivascular space, large Aβ fibrils may be easily trapped between the vascular wall and parenchyma.…”
Section: Introductionsupporting
confidence: 77%
“…In a previous study, we demonstrated that Aβ monomer can be quickly transported through the perivascular space, whereas polymerized Aβ can be trapped at the vascular wall [ 11 ]. These findings, together with those of the present study, suggest that Aβ monomer excreted into the perivascular space can be transported to the subarachnoid space by diffusion based on the concentration gradient, which decreases toward the cortical surface ( Figure 5 B).…”
Section: Discussionmentioning
confidence: 99%